Chronic fluoxetine treatment directs energy metabolism towards the citric acid cycle and oxidative phosphorylation in rat hippocampal nonsynaptic mitochondria - Filipović, Dragana; Findeisen, Peter; Costina, Victor (Brain research, 2017)
Fluoxetine (Flx) is the principal treatment for depression; however, the precise mechanisms of its actions remain elusive. Our aim was to identify protein expression changes within rat hippocampus regulated by chronic Flx treatment versus vehicle-controls using proteomics. Fluoxetine-hydrohloride (15mg/kg) was administered daily to adult male Wistar rats for 3weeks, and cytosolic and nonsynaptic mitochondrial hippocampal proteomes were analyzed. All differentially expressed proteins were functionally annotated according to biological process and molecular function using Uniprot and Blast2GO. Our comparative study revealed that in cytosolic and nonsynaptic mitochondrial fractions, 60 and 3 proteins respectively, were down-regulated, and 23 and 60 proteins, respectively, were up-regulated. Proteins differentially regulated in cytosolic and nonsynaptic mitochondrial fractions were primarily related to cellular and metabolic processes. Of the identified proteins, the expressions of calretinin and parvalbumine were confirmed. The predominant molecular functions of differentially expressed proteins in both cell hippocampal fractions were binding and catalytic activity. Most differentially expressed proteins in nonsynaptic mitochondria were catalytic enzymes involved in the pyruvate metabolism, citric acid cycle, oxidative phosphorylation, ATP synthesis, ATP transduction and glutamate metabolism. Results indicate that chronic Flx treatment may influence proteins involved in calcium signaling, cytoskeletal structure, chaperone system and stimulates energy metabolism via the upregulation of GAPDH expression in cytoplasm, as well as directing energy metabolism toward the citric acid cycle and oxidative phosphorylation in nonsynaptic mitochondria. This approach provides new insight into the chronic effects of Flx treatment on protein expression in a key brain region associated with stress response and memory.